METAFORA DALAM PASAMBAHAN MAANTA MARAPAULAI DI NAGARI TANJUNG KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Pina Herlia Ningsi; Ermanto Ermanto; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of the research is to decribe (1) the metaphor forms in pasambahan maanta marapulai at Nagari Tanjung subsdistrict of Koto VII Sijunjung regency, (2) the meaning of metaphor in pasambahan maanta marapulai at Nagari Tanjung subdistrcit of Koto VII Sijunjung regency, as well as (3) the context of metaphor use in pasambahan maanta marapulai at Nagari Tanjung subdistrict of Koto VII Sijunjung regency. Data of the research is the words in pasambahan maanta marapulai used by citizien at Nagari Tanjung subdistrict of Koto VII Sijunjung regency. The resource of data is pasambahan maanta marapulai from the beginning till pasambahan minta pulang. Data is gained using listening and conversation method, While techniques used is record technique and note technique. Based on the finding, there are fouty four metaphor consisted of 9 metaphor antropomorfis, 12 animal metaphor, 21 metaphor from conrete to abstract as well as 2 metaphor sinaestetik. The meaning of metaphor is based on literal meaning and meaning from the interviwee. While, the context of metaphor use consists of situation and culture context.